Evolutionary Aspects of Huerfano Butte Colorado - Durant, Dolores G. (My University, 1989)
Gabbroic dyke and syenitic plug intrusives have been sampled and studied across Huerfano Butte. Petrography and geochemical analyses were performed on selected specimens; from these analyses chemical variation diagrams have been prepared. Crystal Size Distribution analyses have been done on magnetites and olivines to determine crystal nucleation and growth rate in the dyke. These data have been used to infer aspects of the evolution of Huerfano Butte.
Keywords: evolutionary, Huerfano, Butte, Colorado, dyke, specimens